The emergence and development of foreign concessions in Marrakech Until 1912 (Journal of the College of Basic Education, 2022)
Perhaps one of the most important results of the Industrial Revolution in Europe is the emergence of modern colonial (Imperial) movement in the early of nineteenth century, as well as to other less important reasons. The European countries rushed on the track to race in order to get colonies in Asia, Africa and Latin America. Although Morocco has survived from the Ottoman control, it had remained the focus of attention of the European colonial competition; because of its important strategic location that made it the major interests of the imperial powers. Morocco owned military power, a good business system, adequate financial returns, and political power presented by its Sultans, ministers and loyal leaders, who tried to build a strong state far from the competing countries, still they have been unable to achieve their patriotic goal due to the satirical foreign interventions in the internal affairs of Morocco, especially the interventions of Spain and France since the seventeenth century. Thus, Spain occupied many Moroccans ports and islands refused to abandon them, because Spain considered Morocco a part of the Spanish territory. Britain Returned to occupy the city of Tangier and refused vacating it for geo-strategically reasons. France, on another hand, has been looking forward to occupy the entire Maghreb particularly after the occupation of Algeria in 1830. Morocco suffered during the 19th century from real problems as a result of international competition on its own territory, and these problems widened as the number of the countries which compete to get the maximum amount of privileges and facilities granted by Marrakech to these countries. Because of that, Marrakech entered the whirlpool of treaties imposed on European countries, and the European demands got aggravated, those demands aimed at granting nationals residing in Marrakech privileges and facilities similar to what they get from the natural rights in their countries. Consequently, the foreign hands spanned to cut a wide area of ​​Moroccan power as in the judiciary system, the civil status, inheritance and extensive trade privileges for foreign nationals. In addition, they offered protection system for many of the local, and thus Marrakech lost its authority not only on the arrivals of foreigners only, but also included a wide range of people of the country. And in the end, led foreign aggravated privileges to lose Marrakech political and judicial authority and legislative and economic, and paved the way for the imposition of the French mandate in 1912, with the presence of the Spanish and English presence roosting on parts of its territory